Review on Empirical Studies of Local Impact Effects of Hard Missile on Concrete Structures - Abdul Rahman, Ismail; Ahmad Zaidi, Ahmad Mujahid; Latif, Qadir Bux@ Imran (International Journal of Sustainable Construction Engineering and Technology, 2011)
Concrete is basic construction material used for any kind of structure. However, in most vital and local structures such as nuclear plants, Power plants, Weapon Industries, weapons storage places, water retaining structures like dams, and also local industries, & etc., concrete structures have to be designed as defensive structures to provide protection against any accidents or knowingly generated incidents such as dynamic loading, dynamic local impact damage and global damage generated by kinetic missiles (steel rods, steel pipes, turbine blades, etc.). The impacting missile (projectile) can be classified as ‘Hard’ and ‘Soft’ in nature, depending upon the implication of its deformation with respect to the deformation of target. ‘Hard’ missile impact can generate both local impact damage and also overall dynamic global damage of concrete structure. This paper only provides the review of previous empirical studies related to our study and can be used for making design recommendation and design procedures for determining the dynamic response of the target to prevent local and impact damage.